2007
DOI: 10.1186/1742-5573-4-2
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of routinely collected administrative data in monitoring the incidence of aging dependent hip fracture

Abstract: Societies are facing challenges as the public health burden increases in tandem with population aging. Local information systems are needed that would allow a continuous monitoring of the incidence and effectiveness of treatments. This study investigates the possibilities of routinely collected administrative data as a data source for hip fracture incidence monitoring in Finland.The study demonstrates that a straightforward use of register data results in biased estimates for the numbers of hip fractures. An i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 47 publications
0
25
0
1
Order By: Relevance
“…Osteoporosis and fracture algorithms using diagnostic codes found in administrative databases have been constructed and validated for surveillance purposes [5][6][7][8][9][10][11]. Leslie et al validated algorithms to identify cases of diagnosed osteoporosis using administrative data and demonstrated that a relatively simple algorithm which combined hospitalizations and physician visits could achieve an acceptable level of sensitivity, specificity, and accuracy [5].…”
Section: Introductionmentioning
confidence: 99%
“…Osteoporosis and fracture algorithms using diagnostic codes found in administrative databases have been constructed and validated for surveillance purposes [5][6][7][8][9][10][11]. Leslie et al validated algorithms to identify cases of diagnosed osteoporosis using administrative data and demonstrated that a relatively simple algorithm which combined hospitalizations and physician visits could achieve an acceptable level of sensitivity, specificity, and accuracy [5].…”
Section: Introductionmentioning
confidence: 99%
“…Our data are limited to an 18 month observation period of Medicaid claims from five counties and we do not know how our findings will generalize to longer periods and other populations, including privately insured patients and patients outside the region of study. Further, Medicaid claims have the same issues with validity and bias that have been reported with other administrative databases that can occur due to miscoding of claims and diagnoses (Losina et al 2006;Romano et al 1994;Sund 2007;Walkup and Yanos 2005). However, we believe using at least two claims to diagnose ADHD eliminated some of those problems.…”
Section: Case Studymentioning
confidence: 80%
“…As such, these databases have been valuable in assessing the quality of care received and/or which medical treatments are being performed (Cox et al 2003;Iezzoni 1990Iezzoni , 1997Mitchell et al 1994). Typically, this has been done by using administrative data cross-sectionally to investigate the incidence and treatment of a disease at one instance in time (Asghari et al 2009;Couris et al 2009;Maskarinec 1997;Sund 2007).…”
mentioning
confidence: 99%
“…Estimate for minimum clearance period required to exclude obvious readmissions was obtained using the method based on smoothed hazard function on backward time scale [27]. The basic idea was to detect how long the probability for a new admission due to same reason remains clearly elevated at the population level.…”
Section: Methodsmentioning
confidence: 99%